The Effect of ULLTT on Reducing Pain in Carpal Tunel Syndrome Cases - Lilik Sigit Wibisono; Fitratun Najizah; Ni Kadek Krisna Dwi Patrisia; Lulu'ah Feby Purwanti (The International Science of Health Journal, 2023)
Background: Carpal tunnel syndrome (CTS) is a disorder of the wrist due to narrowing of the carpal tunnel, either due to edema of the fascia in the carpal tunnel or due to abnormalities in the small bones of the hand (carpal bones) resulting in pressure on the median nerve. on the wrist. CTS is defined as weakness in the hands accompanied by pain in the distribution area of the median nerve (Sidharta, 2004). Nerve mobilization is a manipulation technique by moving and stretching nerve tissue to increase axonal transportation so that it can improve nerve conduction. Nerve mobilization can reduce the pressure in the nerves so that there is an increase in blood flow to the nerves, which can have a regenerative and healing effect on injured nerves (Butler, 1991). Nerve mobilization is often used as a form of diagnosis and treatment for musculoskeletal conditions with nerve involvement (Butler, 1991). Nerve mobilization in the Upper Limb Tension Test (ULTT) is carried out at the branches of the Brachial plexus such as the radial nerve, median nerve and ulnar nerve. But here the author only discusses ULTT on the median nerve, namely ULTT 1 which is related to CTS. The aim is to determine physiotherapy management and the effect of Ultrasoundtherapy therapy and nerve mobilization using the ULTT 1 method in cases of Carpal Tunnel Syndrome on reducing pain and increasing the functional ability of the hand. Two group pre test and post test method. Research Place: Physiotherapy clinic, RSU Sidoarjo. TIME: Measuring instrument: Visual Analouge Scale (VAS). Results: treatment using the Mann-Whtney test. With confidence interval (CI) (95%) The results of the study revealed that there was a significant difference in pain in group 1 (p = 0.00) and group 2 (p = 0.00). But there was no significant difference between the two groups in pain improvement (p = 0.152), so there was no better treatment between the two groups. Conclusion: It is concluded that ULTT is useful in treating CTS patients to reduce pain in two groups. The targeted outcomes are publications in national journals indexed by Sinta and HAKI. The TKT target for implementing this gamelan accompaniment exercise is level 2.